PENERAPAN METODE SEMANTIK SEARCH DALAM SISTEM INFORMASI PENCARIAN DOKUMEN KERJA PRAKTEK DAN SKRIPSI BERBASIS WEB - Mitra unik (LPPM Universitas Abdurrab, 2018)
This writing discusses the making of the application search documents practical work and thesis in the Department of Informatics Engineering Faculty of Computer Science Univestias Muhammadiyah Riau. This web-based application uses semantic search method in its search results. This app is designed to generate relevant or easy-to-understand search words by students and also generate words related to search keywords. The goal is to facilitate students in finding reference documents working practice and thesis and to avoid similarity with the previous student topic.